Propuesta de un plan de responsabilidad social empresarial para generar impacto positivo en los STAKEHOLDERS de la Avícola Agropecuaria Santo Domingo S.A.C. para el período 2012 -2016 - Reyes Jacinto, Yvonne Carolina (2012)
This research aims to propose a plan of corporate social responsibility to generate positive impact on the stakeholders of the poultry AgropecuariaSanto Domingo SAC. The research problem is referred to the following question: What extend a social responsibility plan generates positive impact on stakeholders of Agropecuaria Santo Domingo SAC?, Whose hypothesis is: A plan of social responsibility can increase positive impact on the stakeholders Agropecuaria Santo Domingo SAC, highlighting as study variables: independent variable: A plan of social responsibility, and dependent variable: positive impact on the stakeholders of Agropecuaria Santo Domingo SAC. With the development of corporate social responsibility plan the company will implement social responsibility activities that generate greater benefit to its stakeholders and thus be recognized as socially responsible. Descriptive design was used, and the following methods: inductive- deductive and analytic-synthetic. The study population consisted of shareholders, employees, customers, suppliers, residents of the neighboring community Santo Domingo from the district Laredo, its mayor and Prójimo institution, making a total of 746 people, then using stratified sampling, was taken 203 people as sample. Through this research we conclude that although the company makes social responsibility actions, yet it is not considered socially responsible by its environment. And with the implementation of the social responsibility plan the company is going to reach better response to the expectations of its stakeholders.